An isolable, chelating bis[cyclic (alkyl)(amino)carbene] stabilizes a strongly bent, dicoordinate Ni(0) complex - Braulio M. Puerta Lombardi; Morgan R. Faas; Daniel West; Roope A. Suvinen; Heikki M. Tuononen; Roland Roesler (Nature Communications, 2024)
Abstract Chelating ligands have had a tremendous impact in coordination chemistry and catalysis. Notwithstanding their success as strongly σ-donating and π-accepting ligands, to date no chelating bis[cyclic (alkyl)(amino)carbenes] have been reported. Herein, we describe a chelating, C 2-symmetric bis[cyclic (alkyl)(amino)carbene] ligand, which was isolated as a racemic mixture. The isolation and structural characterization of its isostructural, pseudotetrahedral complexes with iron, cobalt, nickel, and zinc dihalides featuring eight-membered metallacycles demonstrates the binding ability of the bis(carbene). Reduction of the nickel(II) dibromide with potassium graphite produces a dicoordinate nickel(0) complex that features one of the narrowest angles measured in any unsupported dicoordinate transition metal complexes.